Comparative changes of health-promoting phytochemicals and sugar metabolism of two hardy kiwifruit (Actinidia arguta) cultivars during fruit development and maturity - Lin, Yuanxiu; Tang, Honglan; Zhao, Bing; Lei, Diya; Zhou, Xuan; Yao, Wantian; Fan, Jinming; Zhang, Yunting; Chen, Qing; Wang, Yan; Li, Mengyao; He, Wen; et al. (Frontiers in Plant Science, 2022)
Hardy kiwifruit (Actinidia arguta) has an extensive range of nutritional and bioactive compounds, and been valued as great resource for kiwifruit breeding. A better understanding of the dynamic changes of composition and accumulation of nutritional compounds during fruit development and ripening is required before genetic or cultural improvements can be targeted. In the present study, the phytochemical analysis of two A. arguta cultivars ‘Yilv’ and ‘Lvmi-1’ showed they comprised different morphology, with a higher fruit diameter while lower vertical fruit diameter of ‘Lvmi-1’ comparing with ‘Yilv’. The antioxidant capacity of both cultivars decreased during the maturity time, and showed no significant difference between ‘Yilv’ and ‘Lvmi-1’. Furthermore, although the glucose gradually increased during the maturity time, the predominant sugar composition was speculated to be fructose in ‘Lvmi-1’ fruit while sucrose in ‘Yilv’ fruit at the early fruit developmental stages. Moreover, the predominant acids in ‘Yilv’ and ‘Lvmi-1’ were citric acid followed by quinic acid, malic acid and oxalic acid. The expression of sugar and starch related genes encoding the crucial enzymes suggested different changes in ‘Yilv’ and ‘Lvmi-1’. Notably, subsequent correlation analysis showed a significant positively correlation between sucrose phosphate synthase (SPS) expression and glucose in ‘Yilv’, fructokinase (FK) expression and starch content in ‘Lvmi-1’, implying their vital roles in sugar and starch accumulation. By contrast, a significant negatively correlation between FK expression and fructose in ‘Lvmi-1’ fruit was observed. In summary, our results provide supplementary information for the dynamic changes of nutritional compounds and antioxidant capacity during hardy kiwifruit maturity time, and give a clue for exploring the mechanism of sugar and starch accumulation in hardy kiwifruit.